The Impoliteness Strategies of Prime Minister Benjamin Netanyahu on Twitter - Khairina Juliana Br Pane; Rahmadsyah Rangkuti; Muhammad Yusuf (Talenta Publisher, 2021)
This study discusses the types of impoliteness strategies and their realization found on Prime Minister Benjamin Netanyahu's Twitter account on Twitter. The idea is used to identify and categorize different sorts of impoliteness methods, as well as how they are implemented. A descriptive qualitative technique was employed for the investigation. According to the findings of this study, Prime Minister Benjamin Netanyahu employs a variety of impoliteness tactics, which are (1) Bald on record impoliteness, (2) Positive impoliteness, (3) Negative impoliteness, and (4) Sarcasm or mock politeness. While withholding politeness was not found in the Prime Minister of the Republic of Indonesia, Benjamin Netanyahu's tweet. Imprudence is the most common category, with 11 tweets accounting for 57.90 percent of the total. Negative impoliteness is ranked second, with 5 tweets (or 26.31 percent) on the list. Next, sarcasm or fake politeness received two tweets, accounting for 10.52 percent of the total. Only one tweet, or 5.26 percent, had a positive impoliteness.